Sex and the City: In the Ambivalent Playground of Postmodern Identity - Doudaki, Vaia (My University, 2012)
The Sex and the City television series marked a shift in televisual discourse regarding the representation of modern women. Flirting with postfeminist narrative and at the same time distancing itself from it, the show offers complex versions of postmodern female identity. The identities of the show's four main female characters are structured in direct relation to sexual, familial and economic freedom and in opposition to patriarchy. The show openly presents issues of women's sexual emancipation offering, however, specific interpretations of this freedom, through policing sex, normalizing some practices and demonizing others. The potentially unlimited freedom for identity reconstruction – a pledge made by the postmodern era and hosted in the series by New York – is bound to be performed in a field of fertile and yet chaotic contradictions with the individual paying the price of the ambivalent consciousness of the possibility to create new identities.
Keywords: Cultural studies; Identity; Television studies; Sex and the City; Postmodernism